Counter-bullying efforts in the perspective of islamic education critical analysis of the animated film a silent voice - Bernadi Setiawan; Muhammad Chafidz Ali Wafa (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research looks at various counter-bullying efforts in films. The aim of this research is to describe counter-bullying efforts and the perspective of Islamic education in counter-bullying efforts in the 2016 animated film A Silent Voice by Naoko Yadama. This type of research uses library research with qualitative research methods and a content analysis technique approach. The primary data source was obtained from the 2016 animated film A Silent Voice by Naoko Yadama and secondary data sources from the internet, magazines, newspapers and books related to counter-bullying efforts from an Islamic education perspective. Data collection techniques using observation and documentation. The data analysis technique for this research uses the following steps: showing films, transferring scenes and dialogue in written form, analyzing content and methods, communicating with relevant books, integrating them with the theoretical framework used, and analyzing. Triangulation of this research data uses source triangulation. The research results show that efforts to counter bullying in the animated film A Silent Voice in general are to prevent bullying victims with coping strategies, and handle bullying cases through psychological intervention approaches. Meanwhile, efforts to counter bullying from an Islamic education perspective are using the example method, habit method, advice method, attention method, and punishment method.